Comparison of the Pharmacokinetics, Safety, and Tolerability of the Autoinjector (AI) and Pre-Filled Syringe (PFS) of SB4 in Healthy Subjects - Shin D; Kim Y; Go A; Velinova M (Dove Medical Press, 2020)
Donghoon Shin,1 Younsoo Kim,1 Ahra Go,1 Maria Velinova2 1Samsung Bioepis Co., Ltd., Incheon, Republic of Korea; 2PRA International, Groningen, the NetherlandsCorrespondence: Donghoon ShinSamsung Bioepis Co., Ltd, 107, Cheomdan-daero, Yeonsu-gu, Incheon 21987, Republic of KoreaTel +82-31-8061-4534Fax +82-31-8061-4393Email dh01.shin@samsung.comPurpose: SB4 is an etanercept biosimilar, approved by the European Commission (EC) and the US Food and Drug Administration (FDA) following a demonstration of equivalent efficacy and safety and comparable quality data to the reference product. This study aimed to demonstrate equivalent pharmacokinetic (PK) profiles, safety, and tolerability between SB4 autoinjector (AI) and SB4 pre-filled syringe (PFS).Patients and methods: This was an open-label, two-period, two-sequence, single-dose, cross-over study to evaluate bioequivalence of PK profiles, safety, and tolerability between SB4 AI and PFS in healthy adults. Treatment periods were separated by 14 days resulting in a 35-day washout between investigational product (IP) administration in Periods 1 and 2.Results: A total of 50 subjects were randomized: 24 subjects in Sequence I and 26 in Sequence II, and 6 subjects discontinued from the study. The primary PK endpoints including area under the concentration–time curve from time zero to infinity (AUCinf) and to the last quantifiable concentration (AUClast), and maximum serum concentration (Cmax) were all within the equivalence margin of 80.00–125.00%. Safety and tolerability were comparable between the two treatments.Conclusion: PK profiles showed that SB4 AI and PFS were bioequivalent in healthy subjects. Safety assessment was also comparable between the two treatments.Keywords: biosimilar, etanercept, bioequivalence, autoinjector, pre-filled syringe